Effects of Retained Austenite and Softened Martensite on High‐Cycle Fatigue Behavior of Spring Steel under Two Loading Modes. Issue 5 (20th January 2023) - Hao, Qingguo; Zhou, Qingsong; Yang, Qi; Zhang, Ke; Yang, Weitao; Zheng, Cheng; Fu, Cong; Rong, Yonghua
Abstract : A novel quenching‐partitioning‐tempering (Q‐P‐T) process is applied to 60Si2Mn spring steel, resulting in multiphase microstructures consisting mainly of retained austenite (RA) and softened martensite (SFM). The influence of multiphase microstructures on the high‐cycle fatigue behavior of Q‐P‐T and traditional quenching and tempering (Q&T) spring steels are investigated under rotating–bending and tension–tension loading. The results indicate that the fatigue strength of Q‐P‐T spring steel with RA, SFM, and lower quenching stress increases by 23.9 and 14.4% under cyclic rotating–bending and tension–tension loadings, respectively, compared with that of Q&T spring steel. Under both loading modes, the fatigue crack of the Q‐P‐T spring steel is mainly initiated from the interface between the martensitic matrix and inclusions or carbides. In contrast, the fatigue crack of the Q&T spring steel is mainly initiated from the plastic area around the martensitic matrix rather than inclusions. The RA, SFM, and lower quenching stress of the Q‐P‐T spring steel are conducive to the formation of dimples and tear ridges in the crack propagation and ultimate failure areas, whereas the inadequate SFM and higher quenching stress of the Q&T spring steel are prone to the formation of quasi‐cleavage facets and secondary cracks. Abstract : The quenching‐partitioning‐tempering (Q‐P‐T) processed spring steel has higher fatigue strengths of 23.9% and 14.4% under cyclic rotating–bending and tension–tension loading, respectively, and exhibits a more ductile failure mode, compared with the quenching and tempering steel. These are mainly attributed to the existence of retained austenite, softened martensite, and lower quenching stress in the Q‐P‐T steel.